Electrochemical Characterization of Na-Ion Charge-Storage Properties for Nanostructured NaTi2(PO4)3 as a Function of Crystalline Order. Issue 9 (1st January 2017) - Ko, Jesse S.; Choi, Christopher S.; Dunn, Bruce; Long, Jeffrey W.
Abstract : We evaluate a series of nanoparticulate NaTi2 (PO4 )3 (NTP) powders as Na + -insertion hosts in either nonaqueous or aqueous electrolyte, correlating electrochemical properties such as capacity and electrode kinetics (in the form of powder–composite electrodes) with the degree of crystallinity in NTP. Starting with amorphous NTP powders prepared using the Pechini method, calcination from 500 to 800°C was used to induce varying degrees of crystallinity and to remove carbonaceous species. Poorly crystalline NTP powders derived by heating at 500–600°C exhibit low specific capacities and broad voltammetric features for Na + -insertion, characteristic of surface-limited processes. Heating at higher temperatures (700–800°C) yields the nanocrystalline form with the NASICON structure. Nanocrystalline NTP exhibits sharp voltammetric peaks and diffusion-limited kinetics in both aqueous and nonaqueous electrolytes. The electrochemical performance of nanocrystalline NTP is further enhanced when integrated with reduced graphene oxide (rGO) to increase local electronic conductivity; theoretical specific capacity for NTP (133 mAh g −1 ) is achieved when NTP-rGO is cycled in a nonaqueous electrolyte, and 100 mAh g −1 in a mild aqueous electrolyte. This nanocomposite also exhibits long-term stability (86% capacity retention after 1000 charge/discharge cycles) in a nonaqueous electrolyte.